PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA TOKO PAKAIAN LIMA R DI PARIAMAN - Asrul Asrul (Ensiklopedia of Journal, 2021)
This study aims to 1) to determine the effect of price on customer loyalty at clothing store Five R in Pariaman 2) to know the influence of service quality to customer loyalty at clothing store Five R in Pariaman 3) to know influence of price and quality of service to customer loyalty at store Five R clothes in Pariaman. The research method is quantitative. The population in this study were consumers or customers of clothing store Five R in Pariaman, where the sample of 35 respondents. The data was processed using SPSS 18.0. Based on the research results can be concluded 1) the price has a positive effect on customer loyalty in clothing store Five R in Pariaman; 2) service quality positively affects customer loyalty at clothing store Five R in Pariaman; 3) price and service quality positively affect customer loyalty at clothing store Five R in Pariaman. With multiple linear regression Y = 5,492 + 0,519 + 0,334 and coefficient of determination equal to 59,2%. To increase sales revenue, the company must provide good service and price in accordance with the quality of products offered.